Everyday technologies in healthcare - Hayre, Christopher M.; Müller, Dave J.; Scherer, Marcia J. (Marcia Joslyn), 1948- (Rehabilitation science in practice series., 2020)
This book examines the role of everyday technology throughout the life cycle in order to demonstrate the wide acceptance and impact of everyday technology and how it is facilitating both practitioners and patients in contemporary practices. In response, then, this text speaks to a number of audiences. Students writing for undergraduate and postgraduate dissertations/proposals will find the array of works insightful, supported with a vast number of references signposting to key texts. For academics, practitioners and prospective researchers this text offers key empirical and methodological insight that can help focus and uncover originality in their own field. We anticipate that readers will find the collection of empirical examples useful for informing their own work, but also, it attempts to ignite new discussions and arguments regarding the application and use of everyday technology for enhancing health internationally. Explores the multifaceted use and application of each everyday technology' that impact on diagnosis, treatment and management of individuals. Examines an array of everyday technologies and how these that can either enhance and/or hinder patient/service user outcomes i.e. handheld devices, computer workstations, gamification and artificial intelligence. Discusses technologies that are intended to facilitate patient diagnosis, practitioner-patient relations, within an array of health contexts. Provides readers with an overview with future direction of everyday technologies and its limitations.